The Characteristics of Diatom in Different Preservation Methods: A Comparation Study - Muhammad Hadi El Amin; Nining Betawati Prihantini (Postgraduate, University of Mataram, 2023)
Diatoms are cosmopolite microalgae with unique characteristics caused of their cells are covered by silica which is called a frustule. Diatom identification is carried out using morphological features that are contained in the frustules. There are some methods for diatom preservation including using Lugolâ€™s iodine, ethanol and formaldehyde solution. This study aims to compare those solutions. Those solutions had prepared with one control and four observations. Lugolâ€™s iodine was prepared with a dose of 1%. Ethanol was used at doses of 20% while the formaldehyde solution was used at 4%. The observed diatom characteristics including the presence of cytoplasm and ornamentation of the diatom frustules (including striae and raphes) were observed to find the distinction in those methods. the presence of cytoplasm in each cell was not too different in the treatment, with the percentage of cytoplasmic cells being 73% (ethanol and formalin) while in Lugol the percentage of cytoplasmic cells was 65% and in the control was 76%.Â Based on the results, it was found that there was no significant effect of differences in preservation methods on cells with the cytoplasm or not with a p-value> 0.05.